2018
DOI: 10.30799/jespr.139.18040302
|View full text |Cite
|
Sign up to set email alerts
|

Household Air Pollution from Burning Biomass for Cooking and Heating – A Review of Health Hazards and Intervention Programs

Abstract: Biomass has been used as a fuel source for cooking and heating for centuries. Despite the emergence of new, efficient, and clean technologies for cooking and heating, biomass is still the primary source of fuel for poor and rural communities in several low and middle income countries around the world. This review presents the chemical composition, the health effects, and the key factors that would enhance the exposure to the emissions of high concentrations of particulate matter, inorganic, and organic chemica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
(102 reference statements)
0
2
0
Order By: Relevance
“…Contamination of foods with PAHs from cooking can be greatly reduced by avoiding smoking or open fires but rather replacing them with gas stoves for cooking [77]. Several nongovernmental organizations and charities offer gas stoves to families to help alleviate this source of food contamination, which is a risk particularly for women and children who spend more time at home [173].…”
Section: Remediationmentioning
confidence: 99%
“…Contamination of foods with PAHs from cooking can be greatly reduced by avoiding smoking or open fires but rather replacing them with gas stoves for cooking [77]. Several nongovernmental organizations and charities offer gas stoves to families to help alleviate this source of food contamination, which is a risk particularly for women and children who spend more time at home [173].…”
Section: Remediationmentioning
confidence: 99%
“…was responsible for numerous respiratory health syndromes -particularly in women and children who used to spend the most time at home cooking, as reported byRoshan and Isaifan (2018) while reviewing health hazards of air pollution from burning biomass for cooking and heating in Asia and Africa and Paulsen et al from electric stoves and these were observed to be 11, 2.8, 1.7 and 1.3 times higher as compared with Nepal's national 24-h indoor air quality standard for PM 2.5 (60 mg/m3). Compilation of data of indoor PM 2.5 of households with wood fuel burning practice and households with nonwood fuel burning practice exhibited significantly (p<0.05) highest value (115.4µg/m 3 ) of indoor PM 2.5 during summer seasons followed by winter season (103.1 µg/m 3 ) and lowest during rainy seasons (95.5 µg/m 3 ) of two year study period with overall average indoor PM 2.5 value of 104.68±44..33 µg/m 3 (Table4) thereby exposing the residents to diseases of the respiratory and cardiovascular systems due to long-term exposure to PM 2.5 pollution.…”
mentioning
confidence: 94%